2022
DOI: 10.3390/ma15134710
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Energetic, and Reactivity Properties of NiPd Alloy Clusters Deposited on Graphene with Defects: A Density Functional Theory Study

Abstract: Graphene with defects is a vital support material since it improves the catalytic activity and stability of nanoparticles. Here, a density functional theory study was conducted to investigate the stability, energy, and reactivity properties of NinPdn (n = 1–3) clusters supported on graphene with different defects (i.e., graphene with monovacancy and pyridinic N-doped graphene with one, two, and three N atoms). On the interaction between the clusters and graphene with defects, the charge was transferred from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…[18][19][20][21][22][23][24] The stability and reactivity of nanoparticles formed by Pd and 3d transition metals deposited on modified graphene have been investigated in some theoretical studies. [25][26][27][28][29] For instance, the stability and reactivity of icosahedral M@Pd 12 (M = Fe, Co, Ni, Cu, Zn, Pd) core-shell nanoclusters deposited on single vacancy graphene (SVG) were investigated employing density functional theory (DFT). 25 The interaction energies between the M@Pd 12 nanoclusters and the SVG were larger than À5 eV, evidencing a remarkable stability of the M@Pd 12 nanoclusters supported on SVG.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…[18][19][20][21][22][23][24] The stability and reactivity of nanoparticles formed by Pd and 3d transition metals deposited on modified graphene have been investigated in some theoretical studies. [25][26][27][28][29] For instance, the stability and reactivity of icosahedral M@Pd 12 (M = Fe, Co, Ni, Cu, Zn, Pd) core-shell nanoclusters deposited on single vacancy graphene (SVG) were investigated employing density functional theory (DFT). 25 The interaction energies between the M@Pd 12 nanoclusters and the SVG were larger than À5 eV, evidencing a remarkable stability of the M@Pd 12 nanoclusters supported on SVG.…”
Section: Introductionmentioning
confidence: 77%
“…In another study, the stability and reactivity of Ni n Pd n (n = 1-3) clusters deposited on SVG and PNG were investigated employing ADFT calculations. 28 It was observed that the Ni n Pd n clusters were more strongly adsorbed on SVG than on PNG. Also, the chemical hardness computed for the Ni n Pd n clusters deposited on modified graphene decreased with respect to the values reported to bare clusters, indicating that the Ni n Pd n /SVG and Ni n Pd n /PNG composites may exhibit greater reactivity than the one of bare Ni n Pd n clusters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another route used to modify the properties of pristine graphene is through substitutional point defects such as doping. This approach substantially modifies the reactivity of pristine graphene [ 95 , 96 , 97 , 98 , 99 , 100 ]. At the DFT level, different types of doping have been investigated to modify the reactivity of graphene [ 61 , 62 , 79 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Hydrogen Storage On Doped Graphenementioning
confidence: 99%